Principles of auditing : an introduction to international standards on auditing - Hayes, Rick Stephan (Upper Saddle River, N.J. ; Harlow : Financial Times Prentice Hall, 2005)
This text offers a structured approach to principles of auditing using International Standards on Auditing as its basis. Written by a team of influential professional auditors with a wealth of teaching experience, this book provides a real world perspective on current auditing practices with coverage of cutting edge developments and techniques.
Rev. ed. of: Principles of auditing / Rick Hayes and Arnold Schilder. c1999.
Includes bibliographical references and index.
oif 18/03/15
Loan
Keywords: Auditing